2019
DOI: 10.1039/c9ra04589a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hydrogen storage performance of graphene nanoflakes doped with Cr atoms: a DFT study

Abstract: Our study reveals that the H2 storage performance of a graphene nanoflake based material could be significantly enhanced through doping with Cr atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 53 publications
4
21
0
Order By: Relevance
“…Still, the reported maximum number of adsorbed H 2 molecules on one Cu atom is three [34]. With respect to what is mention above, one can conclude that the storage ability of doped GS is three H 2 molecules on one transition metal [29][30][31]. The interaction of Cu atom with the H 2 molecule has been also intensively studied in the past [36].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Still, the reported maximum number of adsorbed H 2 molecules on one Cu atom is three [34]. With respect to what is mention above, one can conclude that the storage ability of doped GS is three H 2 molecules on one transition metal [29][30][31]. The interaction of Cu atom with the H 2 molecule has been also intensively studied in the past [36].…”
Section: Introductionmentioning
confidence: 88%
“…The first crucial step in the storage process of the particular gas (in this case H 2 ) is its efficient adsorption on the adsorbent material. It has been shown that the hydrogen molecule exhibits only weak affinity towards the pristine graphene surface [29]. Nevertheless, a number of theoretical studies of hydrogen storage performance of different doped graphene surfaces are rapidly increasing [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations